Double fingerprint characterization of uracil and 5-fluorouracil. (20th August 2021) - Perez-Estebanez, Martin; Cheuquepan, William; Cuevas-Vicario, Jose V.; Hernandez, Sheila; Heras, Aranzazu; Colina, Alvaro
Highlights: A double spectroscopic fingerprint of a molecule is obtained in one experiment. EC-SERS and EC-SOERS provide different spectra of the same analyte. A deprotonated form of the studied analytes is observed during EC-SOERS. This novel methodology exhibits a huge potential for analysis. Abstract: Time Resolved Raman spectroelectrochemistry (TR-Raman-SEC) has been used for the first time to obtain two different Raman spectra of one single analyte in the same experiment. This double detection has been accomplished thanks to the use of electrochemical surface enhanced Raman scattering (EC-SERS) and electrochemical surface oxidation enhanced Raman scattering (EC-SOERS) in the same experiment. These two Raman enhancement phenomena can provide a broad insight into the interaction between analyte and substrate surface when they are combined. To prove the possibilities of this methodology, a Raman spectroelectrochemistry study of uracil (U) and 5-fluorouracil (5-FU), two analytes with relevance in medicine and biochemistry, have been performed. Density functional theory (DFT) calculations has been carried out to shed more light on the interaction of these molecules with silver substrates in acidic media. Graphical abstract: Image, graphical abstract